“Grotesque Faces and Figures”: Child Labourers and Coal Mining Technology in Victorian Nova Scotia - McIntosh, Robert (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1988)
ABSTRACTOne consequence of the technological improvements in mining coal in the nineteenth century was the increased use of child labour in Canadian collieries. Focussing on the major coal-producing province of the period, Nova Scotia, this article outlines how techniques of mining introduced during Victoria's reign encouraged the employment of boys, and how subsequent innovations in mining technology reduced the demand for boy labour after the turn of the century.